COVID-19 and Antiphospholipid Antibodies: Time for a Reality Check? - Favaloro, Emmanuel J.; Henry, Brandon Michael; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2021)
Antiphospholipid antibodies (aPL) comprise a panel of autoantibodies that reflect a potential prothrombotic risk in several autoimmune conditions, most notably antiphospholipid (antibody) syndrome (APS). aPL can be divided into those that form part of the laboratory criteria for APS, namely, lupus anticoagulant (LA), as well as anticardiolipin antibodies (aCL) and anti-β2-glycoprotein I antibodies (aβ2GPI) of the immunoglobulin G and M classes, and those that form a group considered as “noncriteria antibodies.” The noncriteria antibodies include, for example, antiphosphatidylserine antibodies (aPS), antiprothrombin antibodies (aPT), and antiphosphatidylserine/prothrombin complex antibodies (aPS/PT). COVID-19 (coronavirus disease 2019) represents a prothrombotic disorder, and there have been several reports of various aPL being present in COVID-19 patients. There have also been similarities drawn between some of the pathophysiological features of COVID-19 and APS, in particular, the most severe form, catastrophic APS (CAPS). In this review, we critically appraise the literature on aPL and COVID-19. This is a companion piece to a separate review focused on LA. In the current review, we primarily concentrate on the so-called solid phase identifiable aPL, such as aCL and aβ2GPI, but also reflect on noncriteria aPL. We conclude that aPL positivity may be a feature of COVID-19, at least in some patients, but in general, identified “solid-phase” aPL are of low titer and not able to be well-linked to the thrombotic aspects of COVID-19. Also, most publications did not assess for aPL persistence, and where persistence was checked, the findings appeared to represent transient aPL. Importantly, high-titer aPL or multiple aPL positivity (including double, triple) were in the minority of COVID-19 presentations, and thus discount any widespread presence of APS, including the most severe form CAPS, in COVID-19 patients.
Keywords: antiphospholipid antibodies; anticardiolipin antibodies; anti-β2-glycoprotein I antibodies; lupus anticoagulant; COVID-19; microthrombosis; thrombosis